Water-Repellent Improvement of Green Composite Sheet Surface by Hydrophobic Modified-Silica Coating - Munawar, R.F.; Arif, A.B.; Shani, W.N.F.W.A.; Mohamad, N.; Razak, J.A.; Maulod, H.E.A.; Ahsan, Q.; Salleh, M.S.; Hassan, N.H.M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The phenomenon of hydrophobic surface (contact angle of a water droplet exceeding 90°) has attracted a considerable research interest from academia and industry. Current studies have unveiled the fact that the hydrophobicity of a solid surface is governed by surface free energy and surface roughness. To date, many methods have been proposed for fabricating hydrophobic surfaces. In this paper, a facile, low cost, and time-saving approach for the improvement of water-repellent property of durian peel composite sheet surface is studied. A unique mixture of hydrophobic modified-silica particles and polystyrene was synthesised and applied onto the composite sheet via dip coating method. The hydrophobic property was characterised using scanning electron microscopy (SEM) and water contact angle meter. Results show that a water repellent surface with a contact angle of 143.90° was generated, which is nearly superhydrophobic. This method could be an effective strategy for producing hydrophobic surfaces for promising potential applications in water repellency, self-cleaning, friction reduction, and antifouling.